+0  
 
+1
75
1
avatar

 

 

 

 

Help!

Guest Dec 8, 2017
Sort: 

1+0 Answers

 #1
avatar+81022 
+1

 

The sum of the numerator  will be   (x) ( x - 1) / 2

 

So we have that

 

[ (x ) (x - 1) ] / 2

_____________          =    3

          x

 

(x) ( x - 1)

_________              =    3     multiply both sides by 2x

     2x

 

 

x^2 - x  =   6x           subtract   6x from both sides

 

x^2  -7x  =  0         factor

 

x ( x - 7)  =  0      set each factor to 0 and solve for x

 

And   x  = 0    [reject]    or x  =  7

 

 

Proof

 

6/7   + 5/7  +  4/7 + 3/7  + 2/7  +  1/7   =

 

 21 / 7     =    3

 

 

 

cool cool cool

CPhill  Dec 9, 2017

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details